+0  
 
+1
177
11
avatar+302 

I have lost track of these things...

 

Anyway, here is a problem that isn't that hard, really.

 

GIVEN:

a and b are real numbers 

 \(a+b=10\)

 \(a^2+b^2=44\)

                                                               

Find \(a^3+b^3\)

 

Oh, and last time, the question was declared answered after a moderator aswered it, so if possible, please don't declare this question answered so than people can solve it.

 

I encourage everyone who reads this to not look at the other people's answer, so that you can solve it yourself.

Mathhemathh  Aug 10, 2017
edited by Mathhemathh  Aug 10, 2017
edited by Mathhemathh  Aug 10, 2017

Best Answer 

 #3
avatar+18715 
+2

GIVEN:

a and b are real numbers

 \(a+b = 10 \\ a^2+b^2 = 44\)

                                            

Find \(a^3 + b^3\)

 

\(\begin{array}{|rcll|} \hline (a+b)^2 &=& a^2 + 2ab + b^2 \\ (a+b)^2 &=& (a^2 + b^2) +2ab \\ (10)^2 &=& (44) + 2ab \\ 100 &=& 44 + 2ab \quad & | \quad : 2 \\ 50 &=& 22 + ab \\ ab &=& 50-22 \\ \mathbf{ab} & \mathbf{=} & \mathbf{28} \\\\ (a^2+b^2)(a+b) &=& a^3 +a^2b + b^2a + b^3 \\ (a^2+b^2)(a+b) &=& a^3 +b^3 + ab(a+b) \\ 44\cdot 10 &=& a^3 +b^3 + 28\cdot 10 \\ 440 &=& a^3 +b^3 + 280 \\ a^3 +b^3 &=& 440 - 280 \\ \mathbf{ a^3 +b^3} & \mathbf{=} & \mathbf{160} \\ \hline \end{array}\)

 

laugh

heureka  Aug 10, 2017
edited by heureka  Aug 10, 2017
Sort: 

7+0 Answers

 #1
avatar
0

a = 5 - i sqrt(3) ≈ 5.00000 - 1.73205 i and b = 5 + i sqrt(3) ≈ 5.00000 + 1.73205 i
a = 5 + i sqrt(3) ≈ 5.00000 + 1.73205 i and b = 5 - i sqrt(3) ≈ 5.00000 - 1.73205 i

Simplify the following:
(-(i sqrt(3)) + 5)^3 + (i sqrt(3) + 5)^3

(-(i sqrt(3)) + 5)^3 = (-(i sqrt(3)) + 5) (-(i sqrt(3)) + 5)^2:
(-(i sqrt(3)) + 5) (-(i sqrt(3)) + 5)^2 + (i sqrt(3) + 5)^3

(-(i sqrt(3)) + 5)^2 = 25 - 5 i sqrt(3) - 5 i sqrt(3) - 3 = 22 - 10 i sqrt(3):
(-(i sqrt(3)) + 5) -10 i sqrt(3) + 22 + (i sqrt(3) + 5)^3

(-i sqrt(3) + 5) (-10 i sqrt(3) + 22) = 5×22 + 5 (-10 i sqrt(3)) + -i sqrt(3)×22 + -i sqrt(3) (-10 i sqrt(3)) = 110 + -50 i sqrt(3) + -22 i sqrt(3) - 30 = -72 i sqrt(3) + 80:
-72 i sqrt(3) + 80 + (i sqrt(3) + 5)^3

(i sqrt(3) + 5)^3 = (i sqrt(3) + 5) (i sqrt(3) + 5)^2:
80 - 72 i sqrt(3) + (i sqrt(3) + 5) (i sqrt(3) + 5)^2

(i sqrt(3) + 5)^2 = 25 + 5 i sqrt(3) + 5 i sqrt(3) - 3 = 22 + 10 i sqrt(3):
80 - 72 i sqrt(3) + (i sqrt(3) + 5) 10 i sqrt(3) + 22

(i sqrt(3) + 5) (10 i sqrt(3) + 22) = 5×22 + 5×10 i sqrt(3) + i sqrt(3)×22 + i sqrt(3)×10 i sqrt(3) = 110 + 50 i sqrt(3) + 22 i sqrt(3) - 30 = 72 i sqrt(3) + 80:
80 - 72 i sqrt(3) + 72 i sqrt(3) + 80

80 - 72 i sqrt(3) + 80 + 72 i sqrt(3) = 160:
Answer: | 160

Guest Aug 10, 2017
 #2
avatar+302 
+1

#mindblown

#overcomplicated

#i'mimpressed

 

I don't understand that behemoth of a solution because I was too lazy to read it, but you got the right answer, except there is a much, MUCH simpler solution.

Mathhemathh  Aug 10, 2017
 #3
avatar+18715 
+2
Best Answer

GIVEN:

a and b are real numbers

 \(a+b = 10 \\ a^2+b^2 = 44\)

                                            

Find \(a^3 + b^3\)

 

\(\begin{array}{|rcll|} \hline (a+b)^2 &=& a^2 + 2ab + b^2 \\ (a+b)^2 &=& (a^2 + b^2) +2ab \\ (10)^2 &=& (44) + 2ab \\ 100 &=& 44 + 2ab \quad & | \quad : 2 \\ 50 &=& 22 + ab \\ ab &=& 50-22 \\ \mathbf{ab} & \mathbf{=} & \mathbf{28} \\\\ (a^2+b^2)(a+b) &=& a^3 +a^2b + b^2a + b^3 \\ (a^2+b^2)(a+b) &=& a^3 +b^3 + ab(a+b) \\ 44\cdot 10 &=& a^3 +b^3 + 28\cdot 10 \\ 440 &=& a^3 +b^3 + 280 \\ a^3 +b^3 &=& 440 - 280 \\ \mathbf{ a^3 +b^3} & \mathbf{=} & \mathbf{160} \\ \hline \end{array}\)

 

laugh

heureka  Aug 10, 2017
edited by heureka  Aug 10, 2017
 #4
avatar+302 
0

Good job.

Mathhemathh  Aug 11, 2017
 #6
avatar+403 
0

UM HUMM UM UM HUMM

AsadRehman  Aug 11, 2017
 #5
avatar+403 
+1

a = 5 - i sqrt(3) ≈ 5.00000 - 1.73205 i and b = 5 + i sqrt(3) ≈ 5.00000 + 1.73205 i
a = 5 + i sqrt(3) ≈ 5.00000 + 1.73205 i and b = 5 - i sqrt(3) ≈ 5.00000 - 1.73205 i

Simplify the following:
(-(i sqrt(3)) + 5)^3 + (i sqrt(3) + 5)^3

(-(i sqrt(3)) + 5)^3 = (-(i sqrt(3)) + 5) (-(i sqrt(3)) + 5)^2:
(-(i sqrt(3)) + 5) (-(i sqrt(3)) + 5)^2 + (i sqrt(3) + 5)^3

(-(i sqrt(3)) + 5)^2 = 25 - 5 i sqrt(3) - 5 i sqrt(3) - 3 = 22 - 10 i sqrt(3):
(-(i sqrt(3)) + 5) -10 i sqrt(3) + 22 + (i sqrt(3) + 5)^3

(-i sqrt(3) + 5) (-10 i sqrt(3) + 22) = 5×22 + 5 (-10 i sqrt(3)) + -i sqrt(3)×22 + -i sqrt(3) (-10 i sqrt(3)) = 110 + -50 i sqrt(3) + -22 i sqrt(3) - 30 = -72 i sqrt(3) + 80:
-72 i sqrt(3) + 80 + (i sqrt(3) + 5)^3

(i sqrt(3) + 5)^3 = (i sqrt(3) + 5) (i sqrt(3) + 5)^2:
80 - 72 i sqrt(3) + (i sqrt(3) + 5) (i sqrt(3) + 5)^2

(i sqrt(3) + 5)^2 = 25 + 5 i sqrt(3) + 5 i sqrt(3) - 3 = 22 + 10 i sqrt(3):
80 - 72 i sqrt(3) + (i sqrt(3) + 5) 10 i sqrt(3) + 22

(i sqrt(3) + 5) (10 i sqrt(3) + 22) = 5×22 + 5×10 i sqrt(3) + i sqrt(3)×22 + i sqrt(3)×10 i sqrt(3) = 110 + 50 i sqrt(3) + 22 i sqrt(3) - 30 = 72 i sqrt(3) + 80:
80 - 72 i sqrt(3) + 72 i sqrt(3) + 80

80 - 72 i sqrt(3) + 80 + 72 i sqrt(3) = 160:                                      SO THE ANSWER IS 160

AsadRehman  Aug 11, 2017
 #11
avatar+302 
0

Right.

Mathhemathh  Aug 14, 2017

15 Online Users

avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details